Dermatomyositis associated with malignancy: a case highlighting paraneoplastic syndrome - Sanjeev, Chavan Mayuresh; Krishnan, Arun; Jaykaran (International Journal of Research in Medical Sciences, 2025)
Dermatomyositis (DM) is a rare idiopathic inflammatory myopathy characterized by distinctive cutaneous manifestations and progressive, symmetric proximal muscle weakness. It affects both adults and children, with variable clinical presentations and disease severity. The pathogenesis involves autoimmune mechanisms, including complement-mediated microangiopathy, with a potential association with malignancies in adults. In this case study, we report a case of classical DM with incidence of malignancy. Timely diagnosis and administration of steroid led to better prognosis of the patient.